Comparison of Village Fund Formula Policies in Alleviating Poverty - Eri Bukhari; Muhammad Richo Rianto; Supriyanto; Novita Wahyu Setyawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to see whether there was a difference in the number of rural poor people from several policy formulas used in the mechanism for granting the Village Fund which had been running for 6 years. The statistical method used is the Independent Sample T-Test. The sample used is 33 provinces in Indonesia that receive Village Funds sourced from the National Budget and Revenue. The result is that between the first and second formulas there is no difference in the number of rural poor people, as well as between the changes in the second and third formulas. New differences emerged between the third and fourth formulas, but these differences did not show better results, this was also exacerbated by the Covid-19 pandemic that hit the world, including Indonesia.